An Exploration of Uncertainty and Waiting in the Short Story “Rencana Satu Kereta Bersama W Mabelle”: A Formalism and Psychological Analysis - Purnomo, Fazrul Sandi; Harista, Eva; Rahmaniyar, Atik (Raja Zulkarnain Education Foundation, 2025)
This study aims to analyze the themes of waiting and uncertainty in the short story “Rencana Satu Kereta Bersama W Mabelle” by Aravayana, using a formalist and Freudian psychological approach. The formalist approach identifies intrinsic elements such as structure, plot, symbolism, and style, while the Freudian psychological approach explores the personality aspects of the main character through the concepts of the Id, Ego, and Super-ego. This research is conducted qualitatively by analyzing the text of the short story as the primary object. The results reveal that the themes of waiting and uncertainty are represented through symbols such as the